REMOTE E-HEALTH: INTELLIGENT IOT BASED UBIQUITOUS HEALTHCARE SYSTEMS - GOVINDA. K,; SHAIK SHAMA ZABEEN,; ALAPATI SAIJAGATHI,; RAJKUMAR.R, (International Journal of Pharma and Bio Sciences, 2016)
Due to the rapid growth of population and constantly increasing diseases, it’s becoming highly difficult for medically knowledgeable persons like doctors to constantly monitor a patient’s health condition and this has become a very hard task in case of patients from rural areas, where transportation costs incurred to see the best doctors in urban areas. In order to minimize expenses and for emergency care, the health care monitoring system has been brought into picture. This paper proposes a methodology using latest technologies like internet of things to diagnose and monitor the health conditions of patients with minimal medical facilities and improper medication. The data extracted from the patient are transferred to the server locally using the ZigBee Protocol and hosed on the cloud using a WiFi module called ESP-8266. The reason behind storing over the cloud is to obtain a second opinion from medical experts.